The world that changes the world : how philanthropy, innovation and entrepreneurship are transforming the social ecosystem - Cheng, Willie; Sharifah Mohamed (Singapore : Wiley ; Chichester : John Wiley [distributor], 2010)
If there is an X PRIZE for collaborative thought leadership of the social ecosystem, this book would get it. Dr. Peter H. Diamandis. Chairman and CEO, X PRIZE Foundation. The World that Changes the World is thought leadership at its best-envisioning the future through reflection and analysis of past trends and contemporary challenges. Senator the Hon. Ursula Stephens. Australian Parliamentary Secretary for Social Inclusion and the Voluntary Sector. The multifaceted, multinational, multisectoral insights in this volume offer inspiration, ideas, and opportunity for action and impact. Dr. Melissa.
The World that Changes the World; Contents; Acknowledgments; Foreword; Abbreviations; Overview; Beneficiaries; Social Purpose Entities; Capacity Builders; Community; Government; Change Enablers; Macro-Trends; About the Contributors; Index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Social service; Social service -- Forecasting; Service social; Service social; SOCIAL SCIENCE -- Social Work; Social service; Social service -- Forecasting